GPCRs and pain - Stein, Christoph (Henry Stewart Talks, 2019)
Anatomical & physiological principles underlying nociception & pain, Examples of GPCR mediating excitatory & inhibitory effects on pain sensation, Cross-talk between excitatory & inhibitory intracellular signalling pathways (GPCR in sensory neurons), Adverse side effects mediated by opioid receptors in the nervous system, Selective activation of peripheral opioid receptors on sensory neurons in injured tissues, Computational simulation of dynamic opioid receptor-ligand interactions (normal vs. injured), Novel opioid ligand (NFEPP): analgesia in models of inflammatory pain without adverse side effects